(untitled) - Goatly, Andrew (New York, 2011)
Metaphorical and literal language --Metaphor and the dictionary-root analogies --Metaphor and the dictionary - word class and word formation --How different kinds of metaphor work --Relevance theory and the funtions of metaphor --The signalling of metaphor --The specification of topics --The specification of grounds --The interplay of metaphors --Metaphor in its social context; Includes bibliographical references (p. 351-363) and index
Keywords: English language -- Style; Metaphor; Ngôn ngữ Anh -- Phong cách; Phép ẩn dụ